Balancing Charge‐Carrier Transport and Recombination for Perovskite/TOPCon Tandem Solar Cells with Double‐Textured Structures. Issue 5 (20th December 2022) - Zheng, Jingming; Wei, He; Ying, Zhiqin; Yang, Xi; Sheng, Jiang; Yang, Zhenhai; Zeng, Yuheng; Ye, Jichun
Abstract: The ongoing success of tunnel oxide passivating contact (TOPCon) solar cells in the photovoltaic community in conjunction with the continuous advancements in the fabrication technologies of perovskite‐based tandem devices make it possible to access highly‐efficient perovskite/TOPCon tandem solar cells (TSCs). However, the development of such tandem solar cells is still in its infancy. One of the main challenges facing these devices is the balance of passivation and contact properties, especially on the textured crystalline silicon substrates. This article focuses on the double‐textured TOPCon structures, and systematically investigates their passivation and contact properties with the purpose of balancing charge‐carrier recombination and transport properties. The experiment results show that passivation and contact properties of the double‐textured TOPCon structures can be well‐regulated by means of rearranging the schedules of annealing processes and radio frequency powers of SiO x deposition. The mechanisms of charge‐carrier transport on the textured structures are closely studied, suggesting that charge carriers prefer to transport via the valleys of pyramids where the SiO x layer is thin or missing. As a result, the proof‐of‐concept perovskite/TOPCon TSCs featuring the double‐textured structures are successfully fabricated with a remarkable efficiency of 28.49%. Abstract : Passivation and contact performance of double‐textured tunnel oxide passivating contact (TOPCon) structures are promoted by rearranging the schedules of annealing processes and radio frequency powers of depositing SiO x films, and the underlying mechanisms of charge‐carrier transport on the textured structures are closely studied. The proof‐of‐concept perovskite/TOPCon tandem solar cells featuring double‐textured structures are fabricated, yielding an outstanding efficiency of 28.49%.